PROBLEMATIKA PELAKSANAAN MUTU PENDIDIKAN AGAMA ISLAM DI MI WRINGINANOM PONCOKUSUMO MALANG - Amatul Jadidah; Hairul Puadi (Jurnal Tinta, 2021)
Education provides a major contribution to the progress of a nation and is a means of building the character of the nation in building a highly civilized society. It is hoped that Islamic Religious Education will be able to provide new nuances in describing the meaning of developing the quality of Indonesian people, namely humans who believe and have faith in God Almighty.The purpose of this study was to determine the problem of the implementation of Islamic religious education and how to improve the quality of education at Madrasah Ibtidaiyah Al Hikmah in Wringinom, Poncokusumo District, Malang Regency. In this study, the researcher used a naturalistic qualitative type, the conditions emphasized the natural description, data collection or phenomena filtering was carried out from a natural state. Therefore, researchers are seen directly in the field. From the research results, there are several problems found, namely: a). the low level of education acceptance for students b). The low salaries of teachers are due to the economy of guardians of students. c). the lack of educators understanding about the 2013 curriculum.